Parental Digital Mediation and Its Association with the Psychological Well-Being in School-Age Children / Цифровая родительская медиация и ее связь с показателями психологического благополучия детей школьного возраста - RUDNOVA NATALIA A. / РУДНОВА Н.А.; KORNIENKO DMITRY S. / КОРНИЕНКО Д.С.; VOLKOVA ELENA N. / ВОЛКОВА Е.Н.; ISAEVA OKSANA M. / ИСАЕВА О.М. (Наука телевидения)
Digital parental mediation has emerged as a result of the increasing popularity of electronic technologies and their active use in the education of children. Recent research on digital parental mediation highlights the various characteristics that define parental support and control over a child’s digital activity. This study is aimed at determining the relationship between digital parental mediation (parental control and parental support) and the psychological well-being (self-satisfaction and subjective happiness) of adolescents. The characteristics of digital mediation (control and support) are assumed to have opposing effects on the psychological well-being of schoolchildren. The study sample consisted of 4,011 teenagers aged 13 to 15 (M = 14.07, SD = 0.76), 42% of whom were male. In the course of the study, the Digital Parental Mediation Questionnaire, the I myself scale from the questionnaire, the Multidimensional Scale of Student Life Satisfaction, and the Scale of Subjective Happiness were utilized. Statistical processing involved exploratory and confirmatory factor analyses, correlation and regression analyses. As a result, it was confirmed that parental control and support of a child’s digital activity are related, but their effects on psychological well-being vary. Thus, parental support increases a teenager’s satisfaction and happiness, whereas parental control decreases them. This effect is more pronounced in younger adolescents. В связи с распространением цифровых технологий и их активным использованием в образовании детей новой составляющей родительских функция становится цифровая родительская медиация. Исследования цифровой родительской медиации выделяют различные ее составляющие, которые характеризуют родительскую поддержку и контроль цифровой активности ребенка. Целью настоящего исследования стало выявление роли цифровой родительской медиации (родительский контроль и родительская поддержка) в характеристиках психологического благополучия (удовлетворенность собой и субъективное счастье) детей. Предполагается, что характеристики цифровой медиации (контроль и поддержка) вносят разнонаправленные вклады в психологическое благополучие подростков. Выборку исследования составили 4011 школьников в возрасте от 13 до 15 лет (M = 14,07, SD = 0,76), 42% юношей. Использовались методики: опросник цифровой родительской медиации, шкала «Я сам» из опросника «Многомерная шкала удовлетворенности жизнью школьника» и шкала субъективного счастья. Для статистической обработки использовались эксплораторный и конфирматорный факторный анализы, а также корреляционный и регрессионный анализы. В результате было выявлено, что родительский контроль и поддержка цифровой активности ребенка оказываются связанными, но их эффект на психологическое благополучие различен. Так, родительская поддержка повышает удовлетворенность и субъективное счастье подростка, а родительский контроль снижает их. Данный эффект проявляется больше для младших подростков.